Immutability of Distributed Hash Model on Blockchain Node Storage - Rahardja, Untung; Hidayanto, Achmad Nizar; Lutfiani, Ninda; Febiani, Dyah Ayu; Aini, Qurotul (Scientific Journal of Informatics, 2021)
Purpose: The blockchain system uses hash functions. Hash is used in the blockchain to mark each block of data. Hash function algorithms map a string that is usually hexadecimal of any size to a sequence of fixed-size bits. This journal will discuss the distributed hash model for immutable blockchain node storage. Methods: The methodology used in the preparation of this research is mind mapping and literature review, namely the collection of scientific journals, articles, and e-books. Result: Storage of nodes on the blockchain using a distributed hash model. The distributed hash model only stores a portion of the block data at each node, and the block data is taken as a resource. A hash connects each block with the previous on the blockchain, so the entire blockchain transaction cannot be changed or deleted. Novelty: For further research will expand the research topic regarding storage immutability on the blockchain so that it becomes more completed and detailed.